O fluxo informacional para as ações de resposta a desastres naturais em áreas urbanas com base na logística humanitária - Paulucci, Martha Regina Bortolato Cardoso (2013)
This research presents the topic of Natural Disasters and how it has been treated in Brazil and around the world, especially regarding the preparation stage for this confrontation and response, where there are possibilities for logistics support to better serve society affected for such an event. There is much to logistics is being developed in various sectors, from military to business in which they are applied his concepts and techniques to ensure the best balance between the costs of industrial operations, commercial and transportation and customer satisfaction. Currently, several studies have been developed to suit the limited resources to care for victims of disasters being named Humanitarian Logistics. With regard to disaster response operations, many researchers point out that one of the biggest difficulties for logistics activities is the identification of the necessary information, such as demand and its features, which makes the response time inadequate to meet the needs of affected population. This research proposes a starting point for the solution of this issue through the preparation, organization and provision of appropriate information. We performed a literature review about the topic of Natural Disasters and their particularities imply that their phases of pre-impact, impact and post impact, as well as the typical approach front of them related to the various actors responsible. Were exposed to the key concepts and techniques of logistics, humanitarian logistics and information processing. Various data were collected in the literature in order to get a clearer understanding of logistics activities and information that would be useful to decrease the response time, some of the cases studied. It reached a preliminary classification of the main information needs that impact on demand as well as in preparing to meet the same that led to the adaptation of an information flow that enables the provision of information at the initiation stage of the response to policy decision. The integration and provision of appropriate information to administrators Disaster directs better preparation of necessary logistics to respond to natural disasters by reducing the time for the initial collection of information, making the triggering of the response faster, thus improving the quality of care victims.